2018
DOI: 10.1038/s41467-018-03393-8
|View full text |Cite
|
Sign up to set email alerts
|

MRN complex-dependent recruitment of ubiquitylated BLM helicase to DSBs negatively regulates DNA repair pathways

Abstract: Mutations in BLM in Bloom Syndrome patients predispose them to multiple types of cancers. Here we report that BLM is recruited in a biphasic manner to annotated DSBs. BLM recruitment is dependent on the presence of NBS1, MRE11 and ATM. While ATM activity is essential for BLM recruitment in early phase, it is dispensable in late phase when MRE11 exonuclease activity and RNF8-mediated ubiquitylation of BLM are the key determinants. Interaction between polyubiquitylated BLM and NBS1 is essential for the helicase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 46 publications
3
51
0
Order By: Relevance
“…Importantly, SCR7-pyrazine also inhibited the joining of different 5 0 -5 0 noncompatible ends, which requires processing of DNA breaks prior to ligation, and is dependent on classical NHEJ proteins [29,31]. This was also consistent with the observed inhibition of NHEJ by SCR7 [17][18][19][46][47][48]. Besides, similar to SCR7-cyclized, SCR7-pyrazine also showed specific inhibition of joining catalyzed by Ligase IV and their effect on Ligase III, Ligase I, and T4 DNA ligase-mediated joining was minimal in vitro.…”
Section: Scr7-cyclized and Scr7-pyrazine Inhibit Nhej In A Ligase Iv-supporting
confidence: 77%
“…Importantly, SCR7-pyrazine also inhibited the joining of different 5 0 -5 0 noncompatible ends, which requires processing of DNA breaks prior to ligation, and is dependent on classical NHEJ proteins [29,31]. This was also consistent with the observed inhibition of NHEJ by SCR7 [17][18][19][46][47][48]. Besides, similar to SCR7-cyclized, SCR7-pyrazine also showed specific inhibition of joining catalyzed by Ligase IV and their effect on Ligase III, Ligase I, and T4 DNA ligase-mediated joining was minimal in vitro.…”
Section: Scr7-cyclized and Scr7-pyrazine Inhibit Nhej In A Ligase Iv-supporting
confidence: 77%
“…Thus, PARP initiates the cascade of dynamic recruitment of factors, some of which compete with each other, to fine-tune repair pathway choice. Interestingly, a recent study showed that BLM is also recruited to damage sites in a biphasic fashion, initially by the ATM signaling, and subsequently by the MRE11 complex (Tripathi, et al, 2018), suggests that this type of two-step mechanism may be commonly used to ensure versatility and specificity of the factor recruitment.…”
Section: Trf2 Facilitates Intra-chromosomal Hr Repairmentioning
confidence: 99%
“…The recognition of DSBs by the MRN complex (MRE11, RAD50, and NBS1) results in activation of ATM kinase and triggers its autophosphorylation (30). The activated ATM subsequently catalyzes the phosphorylation of a subset of downstream substrates to initiate an early DSB repair response (31, 32). To measure the activation of DDR directly, we analyzed key DDR proteins by Western blot and found that the expression levels of MRE11, RAD50, and NBS1 were strongly increased by RMI1 knockdown in CPT‐treated HeLa cells ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…The data represented are the mean of 3 independent experiments 6 SEM. *P , 0.05, **P , 0.01. subset of downstream substrates to initiate an early DSB repair response (31,32). To measure the activation of DDR directly, we analyzed key DDR proteins by Western blot and found that the expression levels of MRE11, RAD50, and NBS1 were strongly increased by RMI1 knockdown in CPT-treated HeLa cells (Fig.…”
Section: Rmi1 Depletion Activates the Ddr And Causes A Greater G2/m Dmentioning
confidence: 99%